Identification of the vinculin-binding site in the cytoskeletal protein alpha-actinin. - McGregor, A (1994)
Using low-speed sedimentation equilibrium we have established that vinculin binds to alpha-actinin with a Kd of 1.3 x 10(-5) M. Electron microscopy of negatively stained preparations of vinculin revealed spherical particles (diameter 11.2 nm; S.D. 1.7 nm, n = 21), whereas alpha-actinin appeared as a rod-shaped particle (length 33 nm; S.D. 3.3 nm, n = 23). Mixtures of the two proteins contained both 'lollipop'- and 'dumbell'-shaped particles which we interpret as either one or two spherical vinculin molecules associated with the ends of the alpha-actinin rod. We have further defined the vinculin-binding site in alpha-actinin using 125I-vinculin and a gel-blot assay in which proteolytic fragments of alpha-actinin and fragments of alpha-actinin expressed in Escherichia coli were resolved by SDS/PAGE and blotted to nitrocellulose. 125I-vinculin bound to polypeptides derived from the spectrin-like repeat region of alpha-actinin, but did not bind to the actin-binding domain. Binding was inhibited by a 100-fold molar excess of unlabelled vinculin. Using a series of glutathione S-transferase fusion proteins we have mapped the vinculin-binding site to a region toward the C-terminal end of the molecule (alpha-actinin residues 713-749). 125I-vinculin also bound to fusion proteins containing this sequence which had been immobilized on glutathione-agarose beads. The vinculin-binding site is localized in a highly conserved region of the molecule close to the first of two EF-hand calcium-binding motifs.